Laboratory measurements of natural radioactivity in selected igneous rocks of the Opava Mountains region - Dżaluk, Agnieszka; Malczewski, Dariusz; Żaba, Jerzy; Dziurowicz, Maria (Geology, Geophysics and Environment, 2015)
The paper presents results of laboratory gamma–ray measurements of six igneous rocks from the Opava Mountains. The Opava Mountains are located in the Eastern Sudetes and represent their furthest eastern range. They run almost latitudinally along the Polish border with the Czech Republic. The Opava Mountains are situated mostly in the Czech Republic. Only a small fragment between Głuchołazy in the west and Prudnik in the east is situated in Poland (Janeczek et al. 1991) . The study area is built of rocks of different ages and lithologies. The Opava Mountains belong to the western part of the Upper Silesia Block, which together with the Brno Block form a structure that is called the Brunovistulicum. The mountains consist of five structural stages: the Žulova Massif, the Desna Series, the Vbrna Series, the Andělská-Hora Formation and the Horn-Benešov Formation, which run longitudinally (Żaba et al. 2005). The activities of naturally occurring radionuclides were measured using a portable GX3020 gamma-ray workstation. The system is based on a high-purity germanium (HPGe) detector with 32% relative efficiency and energy resolutions of 0.8 keV at 122 keV and 1.7 keV at 1330 keV.). The activity concentrations of 40K varied from 519 Bqkg-1 (paragneiss, Głuchołazy/Mikulice) to 1559 Bqkg-1 (weathered granite, Sławniowice), while those of 228Ac (232Th series) from 7.2 Bqkg-1 (weathered granite, Sławniowice) to 70.6 Bqkg-1 (migmatitic gneiss, Nadziejów). The activities associated with 226Ra (238U series) ranged from 5.5 Bqkg-1 (weathered granite, Sławniowice) to 52.2 Bqkg-1 (gneiss, Kamienna Góra). Measured activity concentrations were compared with the average activity concentration of 40K, 228Ac (232Th) and 226Ra (238U) for similar types of rocks. For the authors’ knowledge, this paper presents the first experimental data concerning activity concentrations of primordial radionuclides in the igneous rocks in the Opava Mountains.